P167 Development of an EORTC module assessing fertility and patients care needs in young cancer patients (phase I-III). (1st November 2019) - Schwab, R; Kiemen, A; Greimel, E; Kesic, V; Weis, J; Hasenburg, A
Abstract : Introduction/Background: Oncological therapy may affect women in terms of future reproductive capabilities. The infertility resulting from the treatment of cancer has a great impact on the quality of life. Patients of reproductive age consider a risk for infertility one of the most difficult components of their illness and treatment. The aim of the EORTC module is the development of an international questionnaire to assess the individual unmet needs and concerns related to fertility issues in young cancer patients. Methodology: We conducted interviews with 13 health care professionals and 12 young cancer patients regarding the topic of fertility preservation and related issues (phase I). The relevant issues were assessed by using thematic analysis of the interviews. Additionally, literature research and discussion with the collaborators at the autumn EORTC meeting 2018 helped to identify important missing topics (phase I). Results: We developed a relevant list of 54 issues in 6 preliminary domains: psychoeducation and counseling; partnership, sexuality and family; financial aspects; quality of life; decision making and coping and global issues (phase I). This list of issues will be translated in national languages. For the next step interviews with young cancer patients and health care professionals during diagnosis and the survivorship continuum will be conducted in eight European countries (phase II and III) for identification of missing issues and to streamline the particular topics with the final goal to develop the international EORTC 'fertility module'. Conclusion: Identification of patients' psychosocial needs is an important part of advanced onco-fertility care including sexual health, intimate relationships and the affordability of fertility preservation measures. This EORTC module will help health care providers to tailor and optimize the individual counseling regarding fertility related issues during cancer diagnosis, treatment and the survivorship continuum and thus to improve the quality of life of young cancer patients. Disclosure: Roxana Schwab: I have received honoraria and expenses from Roche Pharma AG and AstraZeneca GmbH and funding by MacoPharma International GmbH, by Max Planck Institute for Polymer Research Mainz and by Geistlich Biomaterials. Annette Hasenburg: I have received honoraria and expenses from AstraZeneca, FBA Frauenärzte BundesAkademie GmbH, KlarigoVerlag, MedConcept, Med public GmbH, Med update GmbH, Medicultus, Pfizer, Promedicis GmbH, Pierre Fabre Pharma GmbH, Softconsult, Roche Pharma AG, Streamedup! GmbH, Tesaro Bio Germany GmbH. I am consultant to PharmaMar, Promedicis GmbH, Pierre Fabre Pharma GmbH, Roche Pharma AG and Tesaro Bio Germany GmbH. I have received funded research from Celgene. Andrea Kiemen: I have no conflict of interest. E. Greimel: I have no conflict of interest. V. Kesic: I have no conflict of interest. Joachim Weis: This study is supported by an EORTC grant.